Salinity Tolerance of Two Potato Cultivars (Solanum tuberosum) Correlates With Differences in Vacuolar Transport Activity - Jaarsma, Rinse; de Boer, Albertus H. (Frontiers in Plant Science, 2018)
Potato is an important cultivated crop species and since it is moderately salt sensitive there is a need to develop more salt tolerant cultivars. A high activity of Na+ transport across the tonoplast in exchange for H+ is essential to reduce Na+ toxicity. The proton-motive-force (PMF) generated by the V-H+-ATPase and the V-H+-PPase energizes the Na+(K+)/H+ antiport. We compared the activity, gene expression and protein levels of the vacuolar proton pumps and the Na+/H+ antiporters in two potato cultivars (Solanum tuberosum) contrasting in their salt tolerance (cv. Desiree; tolerant and Mozart; sensitive) grown at 0 mM and 60 mM NaCl. Tonoplast enriched vesicles were used to study the pump activity and protein levels of the V-H+-ATPase and the V-H+-PPase and the activity of the Na+/H+ antiporter. Although salt stress reduced the V-H+-ATPase and the V-H+-PPase activity in both cultivars, the decline in H+ pump activity was more severe in the salt sensitive cultivar Mozart. After salt treatment, protein amounts of the vacuolar H+ pumps decreased in Mozart but remained unchanged in the cultivar Desiree. Decreased protein amounts of the V-H+-PPase found in Mozart may explain the reduced V-H+-PPase activity found for Mozart after salt stress. Under non-stress conditions, protein amounts of V-H+-PPase were equal in both cultivars while the V-H+-PPase activity was already twice as high and remained higher after salt treatment in the cultivar Desiree as compared to Mozart. This cultivar dependent V-H+-PPase activity may explain the higher salt tolerance of Desiree. Moreover, combined with reduced vacuolar H+ pump activity, Mozart showed a lower Na+/H+ exchange activity and the Km for Na+ is at least 2-fold lower in tonoplast vesicles from Desiree, what suggests that NHXs from Desiree have a higher affinity for Na+ as compared to Mozart. From these results, we conclude that the higher capacity- in combination with the higher affinity for Na+ uptake can be an important factor to explain the differences in salt tolerance of these two potato cultivars.